Long‐term precipitation and stream discharge records at seven forested experimental watersheds along a latitudinal transect in Japan: Jozankei, Kamabuchi, Takaragawa, Tsukuba, Tatsunokuchi‐yama, Kahoku and Sarukawa. Issue 10 (6th October 2021) - Shimizu, Takanori; Tamai, Koji; Hosoda, Ikuhiro; Noguchi, Shoji; Kominami, Yuji; Abe, Toshio; Kitamura, Kenzo; Kurokawa, Ushio; Levia, Delphis F.; Kubota, Tayoko; Kabeya, Naoki; Iida, Shin'ichi; et al.
Abstract: This data note introduces a database of long‐term daily total precipitation and stream discharge data for seven forested watersheds in Japan that have been continuously monitored by the Forestry and Forest Products Research Institute. Three of the watersheds started data collection in the 1930s. Forest cover across the sites ranges from cool to warm temperate regions with the latitude spanning from 31 to 44° N and annual precipitation ranging from 1200 to 3000 mm yr −1 . The effects of vegetation change via clearcutting, thinning and forest fire (among other stressors) on stream discharge can be analysed from the long‐term observation sites. Moreover, this multi‐site dataset allows for inter‐ and intra‐site comparisons of annual water loss (difference of annual precipitation and stream discharge). These long‐term datasets can provide comprehensive insights into the effects of climate change and other stressors on forested ecosystems, not only in Japan but across a spectrum of forest types, if combined with other long‐term records from other forested watersheds across the world.